Feeling left out: depressed adolescents may atypically recruit emotional salience and regulation networks during social exclusion. Issue 8 (22nd August 2018) - Jankowski, Kathryn F; Batres, Jonathan; Scott, Hannah; Smyda, Garry; Pfeifer, Jennifer H; Quevedo, Karina
Abstract: Depression is associated with negative attention and attribution biases and maladaptive emotion responsivity and regulation, which adversely impact self-evaluations and interpersonal relationships. Using functional magnetic resonance imaging, we investigated the neural substrates of these impairments. We compared neural activity recruited by 126 clinically depressed and healthy adolescents (ages 11–17 years) during social exclusion (Exclusion > Inclusion) using Cyberball. Results revealed significant interaction effects within left anterior insula (AI)/inferior frontal gyrus and left middle temporal gyrus. Insula hyperresponsivity was associated with peer exclusion for depressed adolescents but peer inclusion for healthy adolescents. In additional, healthy adolescents recruited greater lateral temporal activity during peer exclusion. Complementary effect size analyses within independent parcellations offered converging evidence, as well as highlighted medium-to-large effects within subgenual/ventral anterior cingulate cortex and lateral prefrontal, lateral temporal and lateral parietal regions implicated in emotion regulation. Depressogenic neural patterns were associated with negative self-perceptions and negative information processing biases. These findings suggest a neural mechanism underlying cognitive biases in depression, as reflected by emotional hyperresponsivity and maladaptive regulation/reappraisal of negative social evaluative information. This study lends further support for salience and central executive network dysfunction underlying social threat processing, and in particular, highlights the anterior insula as a key region of disturbance in adolescent depression.